Arousal and attention re-orienting in autism spectrum disorders: evidence from auditory event-related potentials - Orekhova, Elena V.; Stroganova, Tatiana A. (Frontiers in Human Neuroscience, 2014)
The extended phenotype of autism spectrum disorders (ASD) includes a combination of arousal regulation problems, sensory modulation difficulties, and attention re-orienting deficit. A slow and inefficient re-orienting to stimuli that appear outside of the attended sensory stream is thought to be especially detrimental for social functioning. Event-related potentials (ERPs) and magnetic fields (ERFs) may help to reveal which processing stages underlying brain response to unattended but salient sensory event are affected in individuals with ASD. Previous research focusing on two sequential stages of the brain response - automatic detection of physical changes in auditory stream, indexed by mismatch negativity (MMN), and evaluation of stimulus novelty, indexed by P3a component, - found in individuals with ASD either increased, decreased or normal processing of deviance and novelty. The review examines these apparently conflicting results, notes gaps in previous findings, and suggests a potentially unifying hypothesis relating the dampened responses to unattended sensory events to the deficit in rapid arousal process. Specifically, ‘sensory gating’ studies focused on pre-attentive arousal consistently demonstrated that brain response to unattended and temporally novel sound in ASD is already affected at around 100 ms after stimulus onset. We hypothesize that abnormalities in nicotinic cholinergic arousal pathways, previously reported in individuals with ASD, may contribute to these ERP/ERF aberrations and result in attention re-orienting deficit. Such cholinergic dysfunction may be present in individuals with ASD early in life and can influence both sensory processing and attention re-orienting behavior. Identification of early neurophysiological biomarkers for cholinergic deficit would help to detect infants “at risk” who can potentially benefit from particular types of therapies or interventions.